Extracellular Oxidoreduction Potential Modifies Carbon and Electron Flow in Escherichia coli - Christophe Riondet; Rémy Cachon; Yves Waché; Gérard Alcaraz; Charles Diviès (2000)
ABSTRACT Wild-type Escherichia coli K-12 ferments glucose to a mixture of ethanol and acetic, lactic, formic, and succinic acids. In anoxic chemostat culture at four dilution rates and two different oxidoreduction potentials (ORP), this strain generated a spectrum of products which depended on ORP. Whatever the dilution rate tested, in low reducing conditions (−100 mV), the production of formate, acetate, ethanol, and lactate was in molar proportions of approximately 2.5:1:1:0.3, and in high reducing conditions (−320 mV), the production was in molar proportions of 2:0.6:1:2. The modification of metabolic fluxes was due to an ORP effect on the synthesis or stability of some fermentation enzymes; thus, in high reducing conditions, lactate dehydrogenase-specific activity increased by a factor of 3 to 6. Those modifications were concomitant with a threefold decrease in acetyl-coenzyme A (CoA) needed for biomass synthesis and a 0.5- to 5-fold decrease in formate flux. Calculations of carbon and cofactor balances have shown that fermentation was balanced and that extracellular ORP did not modify the oxidoreduction state of cofactors. From this, it was concluded that extracellular ORP could regulate both some specific enzyme activities and the acetyl-CoA needed for biomass synthesis, which modifies metabolic fluxes and ATP yield, leading to variation in biomass synthesis.